PELATIHAN KULTUR IN VITRO SEBAGAI UPAYA PELESTARIAN PLASMA NUTFAH ANGGREK SPESIES PADA KOMUNITAS ANGGREK PLANTERUM BANYUMAS - Zulfa Az Zahroh; Zulfa Ulinnuha; Noor Farid (Universitas Mataram, 2026)
Orchids are popular ornamental plants, and their flowers are highly prized for their beauty and variety. Indonesia boasts a rich diversity of orchid species, particularly epiphytic orchids that thrive in forest trees, from Sumatra to Papua. However, orchids are threatened with extinction due to habitat loss and theft. Ex situ conservation efforts using in vitro culture techniques can be undertaken to safeguard the existence of orchid species. The training was conducted to provide insight to the general public and the Planterum orchid hobbyist community regarding orchid conservation and in vitro orchid cultivation. The training was held at the Plant Tissue Culture Laboratory, Faculty of Agriculture, Jenderal Soedirman University in August 2025. A total of 20 participants participated in a series of activities, including sessions on orchid conservation and the basic concepts of in vitro culture techniques, as well as practical sessions on making culture media and planting orchid seeds in vitro. This activity successfully increased the understanding of participants who were previously unfamiliar with in vitro culture techniques to understand the basic concepts and stages of in vitro culture practices as an orchid cultivation technique. 75% of participants were able to recount the composition of the media used to culture orchid seeds and explain the stages of in vitro orchid culture. Activities to introduce the latest technological innovations to the community are useful for improving the quality of the cultivation process and the resulting products.